Back to the Future: Dynamic Contrast Enhanced Photon Counting Detector CT for the Detection of Pituitary Adenoma in Cushing Disease - Mark, Ian T; Van Gompel, Jamie; Bancos, Irina; Nagelschneider, Alex A; Johnson, Derek R; Bathla, Girish; Madhavan, Ajay A; Weber, Nikkole M; Yu, Lifeng (American Journal of Neuroradiology, 2024)
Historically, MRI has been unable to detect a pituitary adenoma in up to half of patients with Cushing disease. This is problematic, as the standard of care treatment is surgical resection, and its success is correlated with finding the tumor on imaging. Photon counting detector CT (PCD-CT) is a recent advancement that has multiple benefits over conventional energy integrating detector CT. We present the use of dynamic contrast enhanced imaging using PCD-CT for detection of pituitary adenoma in patients with Cushing disease.ABBREVIATIONS: PCD-CT ＝ Photon Counting Detector CT; EID ＝Energy-integrating detector; VMI = Virtual monochromatic imaging.